Women in China's long twentieth century - Hershatter, Gail (Global, Area, and International Archive : University of California Press, 2007)
This guide for students of both Chinese and women's history synthesises recent research on women in 20th century China. It surveys over 650 scholarly works, exploring Chinese women in relation to marriage, family, sexuality, labour, and national modernity.